Social health and related factors in nurses: A systematic review and meta-analysis - Khadijeh Sharifi; Zahra Sooki; Zahra Tagharrobi; Leila Ghanbari-Afra (Wolters Kluwer Medknow Publications, 2024)
Background: The present study was conducted to evaluate the level of social health and related factors in nurses. Materials and Methods: This systematic review and meta-analysis were done based on searching English and Persian articles published in PubMed, Scopus, Web of Science, Science Direct databases, Google Scholar, Scientific Information Database, Iranmedex, and Magiran from inception to January 2022. The mean (SD) of nurses' social health scores, their various dimensions, and related factors were extracted from the retrieved articles. Data analysis was performed using Review Manager software, and p < 0.05 was considered significant. Results: A total of 36 studies were reviewed for systematic review and 34 studies for meta-analysis. The total mean (SD) of social health in 9281 nurses was 57.13 (6.82) (on a scale of 0-100) with a 95% confidence interval of 50.31-63.95. Social health of nurses showed a statistically significant relationship with some demographic-personal factors and occupational-organizational factors. Conclusions: The level of nurses' social health was moderate which needs to be improved. To improve the performance of professional roles and the nursing care quality, it is necessary for healthcare system managers, especially nursing managers, to consider individual and organizational factors affecting nurses' social health in planning and decision making and try to increase nurses' social health. Some of the limitations of this study were that only reviewing quantitative cross-sectional studies and couldn't combine words when searching in Iranian databases.